Aplicação de técnicas metaheurísticas para resolver o problema de coordenação de carregamento de veículos elétricos em sistemas de distribuição - Bañol Arias, Maria Nataly [UNESP] (2015)
The main objective of the plug-in electric vehicles (PEV) charging problem is to determine the optimal schedule for charging the PEV batteries with the aim of minimizing the total operational cost of the electrical distribution system in order to obtain an efficient and secure system operation. The optimization techniques used to resolve the plug-in electric vehicles charging problem on electrical distribution systems are two metaheuristic: Tabu Search and GRASP. The mathematical model used to represent the PEV charging problem is a mixed-integer nonlinear programing problem. On the other hand, a hybrid algorithm named GRASP-BT is also proposed in order to improve the solutions obtained by the Tabu Search and GRASP methodologies. The solutions found by the proposed methodologies designate the time periods where each PEV battery connected to the electrical distribution system need to be charged, minimizing the total operational costs, satisfying the operational constraints, considering PEV charging priority and providing quality solution on real time. In order to show the efficiency of the proposed methodologies, a 449 nodes test system with HV and LV network and two sources of distributed generation are used. Test cases consider a 47% and a 63% of PEV penetration